2020
DOI: 10.1002/jor.24778
|View full text |Cite
|
Sign up to set email alerts
|

Orientation anisotropy of quantitative MRI parameters in degenerated human articular cartilage

Abstract: Quantitative magnetic resonance (MR) relaxation parameters demonstrate varying sensitivity to the orientation of the ordered tissues in the magnetic field. In this study, the orientation dependence of multiple relaxation parameters was assessed in cadaveric human cartilage with varying degree of natural degeneration, and compared with biomechanical testing, histological scoring, and quantitative histology. Twelve patellar cartilage samples were imaged at 9.4 T MRI with multiple relaxation parameters, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 49 publications
(99 reference statements)
1
21
0
Order By: Relevance
“…For 400Hz T1ρ, Hänninen et al (2021) reported no significant correlations between PLM retardation (r=0.07, p=0.83) or PLM anisotropy (r=0.20, p=0.53) 26 . The correlation between with PLM angle was also non-significant (rho=-0.517, p=0.089).…”
Section: T1ρmentioning
confidence: 89%
See 2 more Smart Citations
“…For 400Hz T1ρ, Hänninen et al (2021) reported no significant correlations between PLM retardation (r=0.07, p=0.83) or PLM anisotropy (r=0.20, p=0.53) 26 . The correlation between with PLM angle was also non-significant (rho=-0.517, p=0.089).…”
Section: T1ρmentioning
confidence: 89%
“…T2 mapping was studied in relation to PLM in 5 studies (table 2). The relation between T2 mapping and PLM retardation ranged between non-existent (rho=-0.09, p=0.78 26 ) and strong (r=-0.88 41 ). For anisotropy, correlations ranged from rho=0.287, p=0.366) to r=0.87 26,41 .…”
Section: T2mentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, some scholars have found that when studying degeneration of the lumbar intervertebral disc in humans and cadavers, MR-T1ρ imaging is more sensitive than MR-T2WI imaging in the early degeneration of the lumbar intervertebral disc (5). The proteoglycan concentration in the lumbar intervertebral disc nucleus pulposus tissue has been analyzed in many studies, which have found that the proteoglycan concentration has a good and positive correlation with the T1ρ relaxation time value (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to find reliable methods for ex vivo QSM of articular cartilage and to investigate the sensitivity of QSM to different degradation treatments of articular cartilage. Acknowledging the known orientation dependence of several MRI parameters (including QSM) in cartilage, we also investigated the anisotropy of the susceptibility . Because the primary aims of this study were to evaluate methodological aspects as well as the sensitivity of QSM to variations in cartilage properties and constituents, the sample group was chosen to be broad in terms of cartilage degradations, although not very large in size.…”
Section: Introductionmentioning
confidence: 99%